Detection of interictal epileptiform discharges: A comparison of on-scalp MEG and conventional MEG measurements. Issue 8 (August 2020) - Westin, Karin; Pfeiffer, Christoph; Andersen, Lau M.; Ruffieux, Silvia; Cooray, Gerald; Kalaboukhov, Alexei; Winkler, Dag; Ingvar, Martin; Schneiderman, Justin; Lundqvist, Daniel
Highlights: First ever on-scalp magnetoencephalography (MEG) measurement on an epilepsy patient. Twice as many interictal epileptiform discharges seen with on-scalp MEG. Indicates that on-scalp MEG detects more epileptic activity than conventional MEG. Abstract: Objective: Conventional MEG provides an unsurpassed ability to, non-invasively, detect epileptic activity. However, highly resolved information on small neuronal populations required in epilepsy diagnostics is lost and can be detected only intracranially. Next-generation on-scalp magnetencephalography (MEG) sensors aim to retrieve information unavailable to conventional non-invasive brain imaging techniques. To evaluate the benefits of on-scalp MEG in epilepsy, we performed the first-ever such measurement on an epilepsy patient. Methods: Conducted as a benchmarking study focusing on interictal epileptiform discharge (IED) detectability, an on-scalp high-temperature superconducting quantum interference device magnetometer (high-Tc SQUID) system was compared to a conventional, low-temperature SQUID system. Co-registration of electroencephalopraphy (EEG) was performed. A novel machine learning-based IED-detection algorithm was developed to aid identification of on-scalp MEG unique IEDs. Results: Conventional MEG contained 24 IEDs. On-scalp MEG revealed 47 IEDs (16 co-registered by EEG, 31 unique to the on-scalp MEG recording). Conclusion: Our results indicate that on-scalp MEG might capture IEDs not seen by other non-invasive modalities. Significance: On-scalp MEG has the potential of improving non-invasive epilepsy evaluation.